Reses DPRD Sebagai Sistem Keterwakilan Rakyat dalam Pemikiran Abu A’la Al-Maududi - Miinudin (Al-Ulum, 2023)
This study aims to describe regional policy through the function of the recess period based on Article 373 of Law number 17 of 2014 in the Regional People's Representative Council and to describe the function of the recess of the Regional People's Representative Council (DPRD) according to the thoughts of Abû A’lâ al-Maudûdî. This study employs an empirical legal research method with a sociological legal approach. The study's findings demonstrate that in order to administer a country, al-Maudûdî split state administrators' power into three areas: legislative, executive, and judiciary, subsequently known as the trias politica.  According to al-Maudûdî, that every activity and decision taken by the Ahlul Hal wal Aqd / DPRD legislative body, according to al-Maudûdî, must contain the values beneficial value for the people who have chosen him.  However, in reality, the efforts made by individual members of the DPRD are only formal activities and are more concerned with the interests of their party and group and do not absorb the aspirations as a whole of the regions that are their constituents.